Pengaruh Insentif Perpajakan Terhadap Kepatuhan Wajib Pajak UMKM Masa Pandemi Covid-19 : Studi pada salah satu KPP di Kota Bandung - Vega Yulistiani; Maulana Yusup; Robbi Saepul Rahman; S Mia Lasmaya (Acman: Accounting and Management Journal, 2022)
This study aims to determine whether tax incentives affect MSME taxpayer compliance during the covid-19 pandemic and how much influence tax incentives have on MSME taxpayer compliance during the COVID-19 pandemic. This study uses quantitative research methods with a descriptive verification approach. The sample in this study is as many as 44 MSME taxpayers registered in one of the KPP cities of Bandung. Data collection techniques using a questionnaire that has tested for validity and reliability. The data analysis technique used to answer the hypothesis is simple linear regression. The results of data analysis are seen from the coefficient of determination to determine the amount of contribution given by tax incentives to MSME taxpayer compliance by 67%. Furthermore, the results of hypothesis testing can see that the t-count value is 9.259, and the t-table value is 2.018. hypothesis-testing means that the t-count value is greater than the t-table (9.259>2.018). Thus the result is that H0 is rejected and H1 is accepted. Therefore, tax incentives have a positive and significant effect on MSME taxpayer compliance during the COVID-19 pandemic.